1998
DOI: 10.4269/ajtmh.1998.58.232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum antibody responses to Giardia lamblia of symptomatic and asymptomatic patients.

Abstract: The circulating anti-parasite antibody response against Giardia lamblia in symptomatic and asymptomatic Egyptian children with confirmed giardiasis was examined. Symptomatic patients were identified using the following criteria: presence of only G. lamblia cysts in the feces, and one or more of the following symptoms, diarrhea, abdominal pain, loss of weight, vomiting and/or nausea, and abdominal distention. The anti-parasite humoral response was measured using indirect immunofluorescence (IFA), ELISA, and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
2
10
0
2
Order By: Relevance
“…Saliva samples taken from giardiasis patients showed 24 antigen bands with molecular masses varying between 14 and 170 kDa (161). Only one study reported 100% sensitivity of the ELISA, IFA, or Western blot technique in detecting specific antibodies in persons with proven cases of giardiasis (172). The investigators reported a significantly higher titer of circulating antibodies in symptomatic patients than in asymptomatic patients; these results confirmed the results of an earlier study (176).…”
Section: Sensitivity Of Serological Assayssupporting
confidence: 81%
“…Saliva samples taken from giardiasis patients showed 24 antigen bands with molecular masses varying between 14 and 170 kDa (161). Only one study reported 100% sensitivity of the ELISA, IFA, or Western blot technique in detecting specific antibodies in persons with proven cases of giardiasis (172). The investigators reported a significantly higher titer of circulating antibodies in symptomatic patients than in asymptomatic patients; these results confirmed the results of an earlier study (176).…”
Section: Sensitivity Of Serological Assayssupporting
confidence: 81%
“…16 In addition, detection of specific protein bands and serum antibody responses against Giardia species proteins by Western blotting and ELISA has been reported. 6,7,[17][18][19][20][21] Nevertheless, little is known about effect of treatment on specific antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…7 The presence or absence of symptoms has been related to the strain of G. intestinalis, 8,9 to the severity of the infection, 10 or to the immune status of the host. [11][12][13] The potential consequences of asymptomatic giardiasis on nutrient absorption are particularly important in northwestern Mexico, where many children carry this parasite. However, few studies have focused on the potential effects of moderate or asymptomatic giardiasis on nutrient absorption, and thus its effects on the nutritional status of the host.…”
Section: Introductionmentioning
confidence: 99%